Exospheric neutral density at the 10 RE subsolar point during solar maximum: estimates from XMM soft X-ray observations - Jung, Jaewoong; Connor, Hyunju Kim; Carter, Jennifer A.; Koutroumpa, Dimitra; Pagani, Claudio (Frontiers in Astronomy and Space Sciences, 2025)
Highly charged ions in the solar wind undergo charge exchange with neutral atoms in the Earth’s exosphere, particularly within the magnetosheath and cusps. This solar wind charge exchange process generates X-rays, which are expected to be crucial for imaging Earth’s dayside magnetosphere in the upcoming Lunar Environment Heliospheric X-ray Imager (LEXI) and Solar Wind Magnetosphere Ionosphere Link Explorer (SMILE) missions. A key parameter in this process is the density of neutral hydrogen in the Earth’s exosphere. This study estimates the exospheric density during solar maximum using soft X-ray data from the XMM-Newton astrophysics observatory. We used the Open Geospace Global Circulation Model (OpenGGCM), a global MHD model, to calculate plasma density, velocity, and temperature, and then extracted the exospheric density from the soft X-ray data by deconvolving plasma contributions. Based on five XMM-Newton observations during the solar maximum period from 2000 to 2003, we estimate the exospheric density at the 10 RE subsolar point to range from 42.5 to 65.1 cm−3, which is higher than the density used in previous soft X-ray imaging studies. This increased density range suggests stronger X-ray signals for the LEXI and SMILE missions.